-3y-5=1-2y

Simple and best practice solution for -3y-5=1-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-5=1-2y equation:


Simplifying
-3y + -5 = 1 + -2y

Reorder the terms:
-5 + -3y = 1 + -2y

Solving
-5 + -3y = 1 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-5 + -3y + 2y = 1 + -2y + 2y

Combine like terms: -3y + 2y = -1y
-5 + -1y = 1 + -2y + 2y

Combine like terms: -2y + 2y = 0
-5 + -1y = 1 + 0
-5 + -1y = 1

Add '5' to each side of the equation.
-5 + 5 + -1y = 1 + 5

Combine like terms: -5 + 5 = 0
0 + -1y = 1 + 5
-1y = 1 + 5

Combine like terms: 1 + 5 = 6
-1y = 6

Divide each side by '-1'.
y = -6

Simplifying
y = -6

See similar equations:

| 8x+12-20x=5-6x-3 | | 6y+6(y-4)= | | x-3x-9=27 | | 12y+6=6(2y+11) | | 19x^6= | | 4(3x-4)=12(x-1) | | 4a-2-2=6A-3A | | j+5=3 | | 3m+9=30whatsm | | 9k^2=81 | | 3(4-x)=-3(2-x) | | 8-(5-6x)=3(2+3x) | | (3x^2+x+1)-(2x^2-5x+6)= | | Cx+b=a | | a^2-a-63=0 | | 9x+19-22x=4-10x-4 | | (5y-1)=(-2y+4) | | x^2-6x-37=0 | | 0.7(7x+8)=2.7-(x-3) | | 5x+1(-5+2)=18-3 | | 4sqrt(x^2+2x)=4sqrt(3) | | 2x^2-3=x^2+6x | | 5y-7=-169 | | 7n-93=2n-13 | | 4g-3=1g+37 | | X^2+2mx+1=0 | | 23-5n=-3(3-n) | | 17=-7+3n | | x^3-2x=5 | | 9+7=n | | 2*(3x+4)=8*(2x-4) | | (3x^2+x+1)+(2x^2-3x-5)= |

Equations solver categories